Postnatal β2 adrenergic treatment improves insulin sensitivity in lambs with IUGR but not persistent defects in pancreatic islets or skeletal muscle. (29th November 2019) - Yates, Dustin T.; Camacho, Leticia E.; Kelly, Amy C.; Steyn, Leah V.; Davis, Melissa A.; Antolic, Andrew T.; Anderson, Miranda J.; Goyal, Ravi; Allen, Ronald E.; Papas, Klearchos K.; Hay, William W.; Limesand, Sean W.
Abstract : Key points: Previous studies in fetuses with intrauterine growth restriction (IUGR) have shown that adrenergic dysregulation was associated with low insulin concentrations and greater insulin sensitivity. Although whole‐body glucose clearance is normal, 1‐month‐old lambs with IUGR at birth have higher rates of hindlimb glucose uptake, which may compensate for myocyte deficiencies in glucose oxidation. Impaired glucose‐stimulated insulin secretion in IUGR lambs is due to lower intra‐islet insulin availability and not from glucose sensing. We investigated adrenergic receptor (ADR) β2 desensitization by administering oral ADRβ modifiers for the first month after birth to activate ADRβ2 and antagonize ADRβ1/3. In IUGR lambs ADRβ2 activation increased whole‐body glucose utilization rates and insulin sensitivity but had no effect on isolated islet or myocyte deficiencies. IUGR establishes risk for developing diabetes. In IUGR lambs we identified disparities in key aspects of glucose‐stimulated insulin secretion and insulin‐stimulated glucose oxidation, providing new insights into potential mechanisms for this risk. Abstract: Placental insufficiency causes intrauterine growth restriction (IUGR) and disturbances in glucose homeostasis with associated β adrenergic receptor (ADRβ) desensitization. Our objectives were to measure insulin‐sensitive glucose metabolism in neonatal lambs with IUGR and to determine whether daily treatment with ADRβ2 agonist and ADRβ1/β3 antagonists for 1 month normalizes their glucose metabolism. Growth, glucose‐stimulated insulin secretion (GSIS) and glucose utilization rates (GURs) were measured in control lambs, IUGR lambs and IUGR lambs treated with adrenergic receptor modifiers: clenbuterol atenolol and SR59230A (IUGR‐AR). In IUGR lambs, islet insulin content and GSIS were less than in controls; however, insulin sensitivity and whole‐body GUR were not different from controls. Of importance, ADRβ2 stimulation with β1/β3 inhibition increases both insulin sensitivity and whole‐body glucose utilization in IUGR lambs. In IUGR and IUGR‐AR lambs, hindlimb GURs were greater but fractional glucose oxidation rates and ex vivo skeletal muscle glucose oxidation rates were lower than controls. Glucose transporter 4 (GLUT4) was lower in IUGR and IUGR‐AR skeletal muscle than in controls but GLUT1 was greater in IUGR‐AR. ADRβ2, insulin receptor, glycogen content and citrate synthase activity were similar among groups. In IUGR and IUGR‐AR lambs heart rates were greater, which was independent of cardiac ADRβ1 activation. We conclude that targeted ADRβ2 stimulation improved whole‐body insulin sensitivity but minimally affected defects in GSIS and skeletal muscle glucose oxidation. We show that risk factors for developing diabetes are independent of postnatal catch‐up growth in IUGR lambs as early as 1 month of age and are inherent to the islets and myocytes. Key points: Previous studies in fetuses with intrauterine growth restriction (IUGR) have shown that adrenergic dysregulation was associated with low insulin concentrations and greater insulin sensitivity. Although whole‐body glucose clearance is normal, 1‐month‐old lambs with IUGR at birth have higher rates of hindlimb glucose uptake, which may compensate for myocyte deficiencies in glucose oxidation. Impaired glucose‐stimulated insulin secretion in IUGR lambs is due to lower intra‐islet insulin availability and not from glucose sensing. We investigated adrenergic receptor (ADR) β2 desensitization by administering oral ADRβ modifiers for the first month after birth to activate ADRβ2 and antagonize ADRβ1/3. In IUGR lambs ADRβ2 activation increased whole‐body glucose utilization rates and insulin sensitivity but had no effect on isolated islet or myocyte deficiencies. IUGR establishes risk for developing diabetes. In IUGR lambs we identified disparities in key aspects of glucose‐stimulated insulin secretion and insulin‐stimulated glucose oxidation, providing new insights into potential mechanisms for this risk.